Radiation-induced Cataracts in Children With Brain Tumors Receiving Craniospinal Irradiation. Issue 4 (May 2018) - Whelan, Ros J.; Saccomano, Benjamin; King, Robert; Dorris, Kathleen; Hemenway, Molly; Hankinson, Todd C.; Liu, Arthur K.
Abstract : Radiation is a well-known cause of the development of cataracts. For children with brain tumors, craniospinal irradiation (CSI) would be expected to result in a significant risk of cataract development. We reviewed the incidence of cataracts in children with brain tumors who received CSI at our institution. Of 45 children who received CSI and had ophthalmologic examinations, 13 developed cataracts. The median time to develop cataracts was 27.6 months. Seven children underwent surgery for cataract. Given this high incidence of cataracts, we suggest routine eye examinations for all children receiving CSI.